Nnedi Okorafor: magic, myth, morality and the future - Lindow, Sandra J. ca. 20./21. Jh. (Critical explorations in science fiction and fantasy, 2023)
"This work is the first book-length scholarly treatment of Nnedi Okorafor's critically acclaimed fiction. Written for an audience that includes serious fans as well as scholars, it is an introduction to Okorafor's work and major influences. The scope of the text is ambitious, featuring detailed analyses of her novels, short story collection, memoir, comics and graphic novel. Particular emphasis is given to Okorafor's most enduring themes, which include healthy young adult development and decision making, the interweaving of fantasy and science fiction, flight as a unifying force and the use of innovative biotechnology in ecological utopian communities. Influences examined include feminism, Afrofuturist and Africanfuturist movements and African mythology. Chapters also detail Okorafor's examinations of colonialism and corporate neocolonialism in Africa and Africa's potential to become a major world power"--